Astrocytes enable amygdala neural representations supporting memory - Olena Bukalo; Ruairi O’Sullivan; Yuta Tanisumi; Adriana Mendez; Chase Weinholtz; Sydney Zimmerman; Victoria Offenberg; Olivia Carpenter; Hrishikesh Bhagwat; Sophie Mosley; John J. O’Malley; Kerri Lyons; et al. (Nature, 2026)
Abstract Brain systems mediating responses to previously encountered threats provide critical survival functions. Fear memory and extinction are underpinned by neural representations in the basolateral amygdala (BLA) 1–7 , but the contribution of non-neuronal cells, including astrocytes, to these processes remains unresolved. Here, using in vivo calcium (Ca 2+ ) imaging and causal astrocyte manipulations, we find that BLA astrocytes dynamically track fear state and support fear memory retrieval and extinction. By combining astrocyte manipulations with in vivo BLA neuronal Ca 2+ imaging and electrophysiological recordings, we show that astrocyte Ca 2+ signalling enables neuronal encoding of fear memory retrieval and extinction, and readout through a BLA–prefrontal circuit. Our findings reveal a key role for astrocytes in the generation and adaptation of fear-state-related neural representations, revising neurocentric models of critical amygdala-mediated adaptive functions.